(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
This investigation allowed investigating the meanings and meanings that key informants give to ethics in Venezuelan pharmaceutical organizations and, based on the findings, construct a theoretical-axiological approach to managerial ethics in Venezuelan pharmaceutical organizations. To achieve these purposes, the study was oriented with the interpretive paradigm with qualitative approach, as a path to know the reality of the practice of ethics in the management of pharmaceutical organizations that underlies the people who work in them as professionals. It assumes an ontological position of the social reality of a subjective, varied and plural nature, this study is approached from a comprehensive, dialogical and intersubjective epistemological dimension. That is why we resort to interpretation as a methodological path, supported by the phenomenological-hermeneutical method. As a context, two (2) pharmaceutical organizations belonging to the Pharmaceutical Chains and two (2) common pharmaceutical organizations were selected and six (6) pharmaceutical professionals were the protagonists. To collect the information, the in-depth interview was used and the information was analyzed applying the criteria of the categorization and triangulation of the information coming from the different versions. The findings allowed us to generate a theoretical-axiological approach to managerial ethics in Venezuelan pharmaceutical organizations and a series of reflections on the topic studied.